Impact of algorithmic composition on player immersion in computer games: a case study using Markov Chains (Música Hodie, 2018)
The feeling of immersion is an important aspect of gaming experiences. It can be greatly impacted by back- ground music. In this work, we investigate the use of algorithmically-generated background music as a mean to ge- nerate immersion in gaming experiences. For such, we developed two versions of the same game. One of them uses music written by a composer. The other uses real-time generated melodies based on a Markov chain. We evaluated the immersion level related to each of these versions using user questionnaires and performance measures. The re- sults did show only a small immersion difference between the versions. This indicates that algorithmic music can be a suitable option for game content generation.